2014
DOI: 10.1128/jvi.01691-14
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Human Cytomegalovirus UL11 Glycoprotein in Viral Infection and Evaluation of Its Effect on Virus-Specific CD8 T Cells

Abstract: The human cytomegalovirus (CMV) UL11 open reading frame (ORF) encodes a putative type I transmembrane glycoprotein which displays remarkable amino acid sequence variability among different CMV isolates, suggesting that it represents an important virulence factor. In a previous study, we have shown that UL11 can interact with the cellular receptor tyrosine phosphatase CD45, which has a central role for signal transduction in T cells, and treatment of T cells with large amounts of a soluble UL11 protein inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 75 publications
(93 reference statements)
1
31
0
Order By: Relevance
“…Among other specific functions, O-linked glycans may contribute to transport and stable cell surface expression of viral proteins. This has been suggested for HCMV UL11 and for VZV gB (28,110). Interestingly, we identified an ambiguous site FIGURE 3.…”
Section: Discussionsupporting
confidence: 55%
“…Among other specific functions, O-linked glycans may contribute to transport and stable cell surface expression of viral proteins. This has been suggested for HCMV UL11 and for VZV gB (28,110). Interestingly, we identified an ambiguous site FIGURE 3.…”
Section: Discussionsupporting
confidence: 55%
“…pUL11 may therefore be more likely to affect CD4 T cell function in vivo . It may also be for this reason that HCMV specific CD8 T cell secretion of IFNγ was not affected by the presence of pUL11 on infected cells [35], in contrast to the results presented here for IL-10 secretion, which is preferentially produced by CD4 T cells [19]. The UL11 protein seems likely to play a role in vivo ; antibodies to pUL11 have been found in patient sera, implying that the protein is expressed at detectable levels [85].…”
Section: Discussionmentioning
confidence: 99%
“…HCMV ΔUL11 is based on the same BAC, but with a deletion of the UL11 ORF and containing the ORF encoding gaussia luciferase in its place (for construction see[35], HCMV HM11DL mutant).…”
Section: Methodsmentioning
confidence: 99%
“…T lymphocytes are known to have fundamental roles in controlling HCMV infection, while the virus has also evolved to develop immune evasion mechanisms. For example, it has been demonstrated that the UL11 gene product (pUL11) interferes with the activation and proliferation of T cells 24 , 29 . Because of the sequence similarity between pUL10 and pUL11, exposure of T cells to pUL10 may also hamper proliferation upon cellular activation.…”
Section: Resultsmentioning
confidence: 99%